2013
DOI: 10.2147/opth.s48364
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of an intravitreal dexamethasone implant (Ozurdex®) in patients with persistent diabetic macular edema

Abstract: BackgroundTo evaluate the efficacy and safety of an intravitreal dexamethasone implant (Ozurdex®; Allergan Inc, Irvine, CA, USA) in patients with persistent diabetic macular edema (DME) over a 6-month follow-up period.MethodsSeventeen patients (20 eyes) affected by DME were selected. The mean age was 67 + 8 years, and the mean duration of DME was 46.3 + 18.6 months. The eligibility criteria were: age ≥ 18, a best-corrected visual acuity between 5 and 40 letters, and macular edema with a thickness of ≥275 μm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 23 publications
4
55
1
18
Order By: Relevance
“…[17][18][19] IVD delivers sustained release of corticosteroid and has proven to be an effective treatment modality for DMO. [9][10][11][12] Corticosteroids block production of inflammatory cytokines and VEGF, 27 inhibit leukostasis, 28 improve the barrier function of vascular endothelial cell tight junctions, 29 inhibit endothelial nitric oxide synthase, 30 reduce tissue oedema, and decrease the release of prostaglandins and histamines, 31 all of which could cause vasodilation and choroidal thickening, potentially affecting ocular perfusion pressure. 32 IVD, therefore, could exert its therapeutic effect not only on the retina, but also on the choroid, by decreasing the production of inflammatory cytokines and factors that could increase CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] IVD delivers sustained release of corticosteroid and has proven to be an effective treatment modality for DMO. [9][10][11][12] Corticosteroids block production of inflammatory cytokines and VEGF, 27 inhibit leukostasis, 28 improve the barrier function of vascular endothelial cell tight junctions, 29 inhibit endothelial nitric oxide synthase, 30 reduce tissue oedema, and decrease the release of prostaglandins and histamines, 31 all of which could cause vasodilation and choroidal thickening, potentially affecting ocular perfusion pressure. 32 IVD, therefore, could exert its therapeutic effect not only on the retina, but also on the choroid, by decreasing the production of inflammatory cytokines and factors that could increase CT.…”
Section: Discussionmentioning
confidence: 99%
“…6 Intravitreal dexamethasone implants (Ozurdex; Allergan, Irvine, CA, USA) is a sustained-release biodegradable implant, and it was shown to be effective for the treatment of DMO. 7,8 Recent studies showed that certain eyes with DMO were resistant to anti-VEGF therapy, 9 and intravitreal injection of dexamethasone (IVD) implant has proven to be a novel treatment modality for persistent DMO, 10,11 DMO in difficult to treat vitrectomized eyes, 12 and particularly in cases unresponsive to multiple injections of anti-VEGF agents. 9 With the advent of enhanced depth imaging optical coherence tomography (EDI-OCT), changes in choroidal thickness (CT) have been reported in chorioretinal diseases such as DMO, age-related macular degeneration, and uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence in the published literature of the effect of DEX-DDS in the treatment of edema persisting following other treatments [28,29,30,31,32,33]. The purpose of our study was to examine the effect of DEX-DDS in patients with severely recalcitrant CME that had a poor or short-term response to other treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…[80][81][82][83][84][85] In the first study, Zucchiatti et al 80 showed that a single intravitreal injection of Ozurdex produced improvement in BCVA and FT in eyes with persistent DMO. Such improvement was evident from the third day to the first month after injection, peaked at the third month and was no more significant 6 months after the injection.…”
Section: Interventional Case Series Studiesmentioning
confidence: 99%
“…82 Seventeen patients (20 eyes) affected by DMO were selected. Thirteen patients had also previously been treated with anti-VEGF medication.…”
Section: Interventional Case Series Studiesmentioning
confidence: 99%